Polarized radiative transfer considering thermal emission in semitransparent media - 贲勋 易红亮 谈和平 (Chinese physics B, 2014)
The characteristics of the polarization must be considered for a complete and correct description of radiation transfer in a scattering medium. Observing and identifying the polarizition characteristics of the thermal emission of a hot semitransparent medium have a major significance to analyze the optical responses of the medium for different temperatures. In this paper, a Monte Carlo method is developed for polarzied radiative transfer in a semitransparent medium. There are mainly two kinds of mechanisms leading to polarization of light： specular reflection on the Fresnel boundary and scattering by particles. The determination of scattering direction is the key to solve polarized radiative transfer problem using the Monte Carlo method. An optimized rejection method is used to calculate the scattering angles. In the model, the treatment of specular reflection is also considered, and in the process of tracing photons, the normalization must be applied to the Stokes vector when scattering, reflection, or transmission occurs. The vector radiative transfer matrix （VRTM） is defined and solved using Monte Carlo strategy, by which all four Stokes elements can be determined. Our results for Rayleigh scattering and Mie scattering are compared well with published data. The accuracy of the developed Monte Carlo method is shown to be good enough for the solution to vector radiative transfer. Polarization characteristics of thermal emission in a hot semitransparent medium is investigated, and results show that the U and V parameters of Stokes vector are equal to zero, an obvious peak always appear in the Q curve instead of the I curve, and refractive index has a completely different effect on I from Q.